2017
DOI: 10.1111/ina.12426
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and pro-inflammatory responses of spore and hyphae samples from various mold species

Abstract: Mold particles from Aspergillus fumigatus, Penicillium chrysogenum, Aspergillus versicolor, and Stachybotrys chartarum have been linked to respiratory-related diseases. We characterized X-ray-inactivated spores and hyphae fragments from these species by number of particles, morphology, and mycotoxin, β-glucan and protease content/activity. The pro-inflammatory properties of mold particles were examined in human bronchial epithelial cells (BEAS-2B) and THP-1 monocytes and phorbol 12-myristate 13-acetate (PMA)-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 63 publications
3
26
0
1
Order By: Relevance
“…The outdoor levels of fragments reported by Delfino et al and the workplace levels reported by Madsen and co-authors were associated with asthma symptom exacerbations and acute ODTS, respectively. Based on these results and given that fungal hyphae from common species like Aspergillus fumigatus and Penicillium chrysogenum are immunologically more potent than their spores ( Hohl et al, 2005 ; Aimanianda et al, 2009 ; Øya et al, 2018 ), the exposure levels of fungal fragments observed in sawmills may be linked to adverse health effects in sawmill workers.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The outdoor levels of fragments reported by Delfino et al and the workplace levels reported by Madsen and co-authors were associated with asthma symptom exacerbations and acute ODTS, respectively. Based on these results and given that fungal hyphae from common species like Aspergillus fumigatus and Penicillium chrysogenum are immunologically more potent than their spores ( Hohl et al, 2005 ; Aimanianda et al, 2009 ; Øya et al, 2018 ), the exposure levels of fungal fragments observed in sawmills may be linked to adverse health effects in sawmill workers.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study exposing differentiated macrophages to spores and mycelial fragments from A. fumigatus, A. versicolor, P. chrysogenum , and S. chartarum revealed species and particle type dependent inflammatory potency. Fragments from A. fumigatus and P. chrysogenum showed higher inflammatory effects compared to spores whereas the inverse was observed with A. versicolor and S. chartarum ( Øya et al, 2018 ). The presence of hydrophobin rodlet layers on spores has been suggested to explain these differences in immune reactions by shielding immune potent surface constituents on spores from A. fumigatus .…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, we may get new insights in the role played by fungi in respiratory morbidity when we base our characterization on a holistic approach. Secondly, the paradigm of spores as the major fungal exposure particles bearing allergens and fungal metabolites has changed upon the discovery of large numbers of submicron fragments and the differences in the immunological responses to spores as compared to hyphae as revealed by experimental studies . Submicron fragments were suggested as the most prevalent fungal particles in indoor exposure .…”
Section: Discussionmentioning
confidence: 99%
“…There are insufficient data on the mechanism of S. marginatum L. f. proteins action on normal blood mononuclear cells. Nevertheless, could be related to the ability of cells to adapt to the effects of proteins involved in chemotactic effects (Alfaro Leon et al, 2005), such as serine proteases capable of producing cytokines (IL-4, IL-10 and TGF-β) (de Matos Guedes et al, 2010;Øya et al, 2018).…”
Section: Discussionmentioning
confidence: 99%